Rapid yield loss of rice cropped successively in aerobic soil - George, Thomas; Magbanua, Roger; Garrity, Dennis P.; Tubaña, Brenda S.; Quiton, Jonathan (Wiley, 2002)
Upland rice (Oryza sativa L.), commonly considered to be low yielding, can be high yielding if the genotype is improved for harvest index (HI) and the crop is grown relatively free from nutrient and drought stresses. We examined whether high and stable rice yields could be obtained in aerobic soil. In four experiments of 1‐ to 3‐yr duration, lime, N, and P were inputs for wet‐season upland rice ‘UPLRi‐5’ in a favorable rainfed Oxisol. In a 3‐yr experiment consisting of two crops per year in an irrigated Ultisol, different lowland and upland varieties were grown in limed and fertilized aerobic soil. First‐season rainfed UPLRi‐5 yield varied from 1.5 to 7.4 Mg ha−1, with low yields in fields receiving low early‐season rainfall. With irrigation, the lowland hybrid ‘Magat’ yielded 7.8 Mg ha−1 vs. 2.1 Mg ha−1 for traditional upland rice ‘Lubang Red’. Magat's high yield was associated with a HI of 0.43 in contrast to 0.31 of improved upland rice variety ‘Apo’ and 0.17 of Lubang Red. Whether the crop was rainfed or irrigated, yield loss was rapid following the first season: Grain yields decreased by up to 73% for rainfed UPLRi‐5 in the second to third season. In the irrigated upland, yield loss in the second to fourth season was reflected in a 16 to 79% decline in 10‐wk biomass. Here, the 13‐wk biomass in the fifth crop was only half that of the simultaneously grown first‐season crop. We conclude that while promise exists for high‐yielding rice in aerobic soil, the rapid yield loss with successive rice cropping must first be overcome.